"Reckoning with Colin Rowe: ten architects take position" - Sanz Esquide, José Ángel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2016)
Reckoning With Colin Rowe es un pequeño, pero muy inteligente y desinhibido, libro sobre Colin Rowe, publicado después de su fallecimiento y editado por el arquitecto, escritor y profesor Emmanuel Petit. En él se recogen una selección de textos realizados ex profeso por los siguientes autores: Robert Maxwell, Anthony Vidler, Peter Eisenman, O. Mathias Ungers, Léon Krier, Rem Koolhaas, Alan Colquhoun, Bernhard Hoesli, Bernard Tschumi y Robert Slutzky. Todos arquitectos, a excepción del último que es pintor. Autores muy variados, de diversas generaciones y de muy distinta procedencia que mantuvieron cierta relación con Rowe, que escriben desde un breve texto hasta los más amplios y abarcadores, combinando la forma del ensayo con la entrevista, con el propósito de valorar su legado. Palabras clave: Manierismo, Contra el Zeitgeist, Trasparencia, Collage, Montaje Reckoning With Colin Rowe is a small, but very intelligent and uninhibited, book about Colin Rowe, published after his death and edited by architect, writer and teacher, Emmanuel Petit. The book collects a selection of articles, written specificically for this issue by the following authors: Robert Maxwell, Anthony Vidler, Peter Eisenman, O. Mathias Ungers, Léon Krier, Rem Koolhaas, Alan Colquhoun, Bernhard Hoesli, Bernad Tschumi and Robert Slutzky, all of them architects, with the exception of the last one, who is a painter. All very different authors, from different generations and from very different backgrounds, that maintained a certain relationship with Rowe. They have written texts that vary from essay to interview and from short to more extensive and comprehensive texts, in order to asses his legacy. Keywords: Mannerism, Opposing Zeitgeist, Trasparency, Collage Montage